Detecting the likelihood of fraudulent financial reporting: an analysis of fraud diamond / Reni Yendrawati, Huda Aulia and Hendi Yogi Prabowo. - Yendrawati, Reni; Aulia, Huda; Prabowo, Hendi Yogi (Faculty of Business and Management and UiTM Press Universiti Teknologi MARA, Malaysia., 2019)
This paper aims to analyze the likelihood of fraudulent financial reporting using the fraud diamond analysis. Fraud diamond is a concept explaining factors that cause someone to commit fraud, namely pressure, opportunity, rationalization, and capability. In this research, pressure factor was proxied by using financial stability, external pressure, and financial target. Opportunity factor was proxied by using the nature of industry and effectiveness of monitoring. Rationalization factor was proxied by rationalization and capability was proxied by capability. This research made use of earnings management to discover the likelihood of financial statement frauds. Earnings management was measured by using F-score indicator. The population in this research were manufacturing companies listed on the Indonesian Stock Exchange (IDX) from the year 2014 – 2016. From the population, 31 companies were selected as the research samples by using the purposive sampling method.  This quantitative method-using research was analyzed using multiple regression analysis and T-tests for hypotheses testing. The research findings reveal that only the opportunity variable proxied by industrial nature is proven to have an influence in detecting the likelihood of fraudulent financial reporting. In the meantime, other variables have no influence in detecting the likelihood of fraudulent financial reporting.